The Experiental Tourism: Dari Bangunan Bersejarah Hingga Aktivitas Wisata Di Kawasan Pecinan Lasem - Vyana Lohjiwa; Adika; Ahmad Taufik; Raynata Gyshovadhira; Salma Hanifa Irliana; Maria Andini Supriyadi (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2021)
Sustainable tourism is an activity of applying the idea of ​​sustainable development, there has been change in tourist behavior from passive to active tourists. Tourists are no longer satisfied just being an observer but are more interested in experiencing, this is the main idea in the concept of experiential tourism, with the application of this concept many tourist destinations experience a sustainable tourism cycle. This research tries to examine the concept of experiential tourism using the tourist on site experience model, the aspects studied include activities, resources, and conceptions in the Pecinan Lasem area. Lasem has a big potential for historical buildings, acculturation of Chinese and Javanese culture, tolerance of religions from Hinduism, Buddhism, and Islam which produces Lasem Batik wrapped into a tourist activity. This research using a descriptive method with qualitative approach. The research show that Pecinan Lasem can be said as an experiential tourism seen from the historical buildings that have become icons of acculturation of Chinese and Javanese culture to the tourism activities it offers.